Application Of Response Surface Methodology (RSM) For The Optimization Parameters Of Hydrochar Production From Coconut Husk Using Hydrothermal Carbonization - Zahrimi, Mohamad Mifzal Nur Hakim (Universiti Sains Malaysia, 2021)
An ideal and optimum conditions for maximum production of hydrochar yield of coconut husk via hydrothermal carbonization (HTC) were investigated using optimization method. The optimization and analysis of significant operating conditions which were reaction temperature and residence time was done based on the experiment conducted in the previous study at hydrothermal carbonization temperature range from 180 to 240°C and 48 to 96 h. The simulation was carried out to study the effect of operating conditions (reaction temperature, residence time and biomass-water ratio) on hydrochar through hydrothermal carbonization of coconut husk with the range taken from previous studies at 180-260°C, 0.5-2 h and 1:5-1:15 wt% respectively. Simulation data was optimized and analysed by using response surface methodology (RSM) in Design Expert to design the experiments. Based on chosen Central Composite Design (CCD) method, a quadratic model was developed to correlate the operating conditions and hydrochar yield. The optimized hydrochar yield from the experiment conducted in previous study was obtained at 60.669% at 194.121°C and 48 h. From the simulation data, hydrochar yield was obtained at 70.909% at 180°C, 0.5 h and 1:15 wt%.